Long directed (s,t)-path: FPT algorithm - Fomin, Fedor V.; Lokshtanov, Daniel; Panolan, Fahad; Saurabh, Saket; Zehavi, Meirav (Information processing letters, 2018)
Given a digraph G, two vertices s,t∈V(G) and a non-negative integer k, the Long Directed(s,t)-Path problem asks whether G has a path of length at least k from s to t. We present a simple algorithm that solves Long Directed(s,t)-Path in time O⋆(4.884k). This results also in an improvement upon the previous fastest algorithm for Long Directed Cycle. •Single-exponential time parameterized algorithm for long directed (s, t)-path.•The algorithm is simple and intuitive.•Consequently, we also obtain an improvement for long directed cycle.